Advanced cardiac imaging - Nieman, Koen; Gaemperli, Oliver; Lancellotti, Patrizio; Plein, Sven (Woodhead Publishing series in biomaterials, 2015)
Advances in Cardiac Imaging presents the latest information on heart disease and heart failure, major causes of death among western populations. In addition, the text explores the financial burden to public healthcare trusts and the vast amount of research and funding being channeled into programs not only to prevent such diseases, but also to diagnose them in early stages. This book provides readers with a thorough overview of many advances in cardiac imaging. Chapters include technological developments in cardiac imaging and imaging applications in a clinical setting with regard to detecting various types of heart disease